2000
DOI: 10.1007/s12064-000-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

On some theoretical grounds for an organism-centered biology: Property emergence, supervenience, and downward causation

Abstract: In this paper, we investigate some theoretical grounds for bridging the gap between an organism-centered biology and the chemical basis of biological explanation, as expressed in the prevailing molecular perspective in biological research. First, we present a brief survey of the role of the organism concept in biological thought. We advance the claim that emergentism (with its fundamental tenets: ontological physicalism, qualitative novelty, property emergence, theory of levels, irreducibility of the emergents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…The notion of downward causation has been examined and referred to mainly in discussions about reductionism, emergentism, hierarchical levels of biological organization, evolutionary epistemology, mental supervenience, systems biology, and complex systems theory (Campbell 1974;Popper 1978;Sperry 1986;Kim 1992;Juarrero 1999;El-Hani and Emmeche 2000;Andersen et al 2000;Bickhard and Campbell 2003;Soto and Sonnenschein 2005;Noble 2006;Bedau 2008;Mitchell 2009). Currently, significant discussion is underway not only with respect to the aforementioned topics but also for the whole conceptual framework of contemporary theoretical biology.…”
Section: Campbell and His Causation Proposalmentioning
confidence: 99%
“…The notion of downward causation has been examined and referred to mainly in discussions about reductionism, emergentism, hierarchical levels of biological organization, evolutionary epistemology, mental supervenience, systems biology, and complex systems theory (Campbell 1974;Popper 1978;Sperry 1986;Kim 1992;Juarrero 1999;El-Hani and Emmeche 2000;Andersen et al 2000;Bickhard and Campbell 2003;Soto and Sonnenschein 2005;Noble 2006;Bedau 2008;Mitchell 2009). Currently, significant discussion is underway not only with respect to the aforementioned topics but also for the whole conceptual framework of contemporary theoretical biology.…”
Section: Campbell and His Causation Proposalmentioning
confidence: 99%
“…Differences in animal designs and complexity, for instance, are mostly related to changes in the temporal and spatial regulation of patterns of gene expression (Carroll et al, 2005), and not so much to the evolution of genes themselves, as shown by sequence comparison between several animal genomes. Regulation is a process that entails an influence of higher-level processes on molecular processes, such as transcription, RNA splicing, translation etc., i.e., it involves a kind of process which has not been clearly conceptualized yet in biological thought, namely, downward determination (see, for instance, Campbell, 1974;Andersen et al, 2000;El-Hani and Emmeche, 2000;El-Hani and Queiroz, 2005). The time and place in which a given set of genes is or is not activated depend crucially on downward regulation, and this regulation is something to which genes are subjected, and not something that genes do, command, control, program, etc.…”
Section: The Classical Molecular Gene Conceptmentioning
confidence: 99%
“…", should be posed in connection with this particular interpretation. This raises a number of difficult questions, as the problem of downward causation (DC) is the most debated in the contemporary literature on emergence (see, e.g., Schröder 1998;Stephan 1999;Andersen et al 2000;El-Hani & Emmeche 2000;El-Hani 2002;Hulswit, in press). Therefore, we will not pursue this debate here in all its details.…”
Section: Modes Of Irreducibilitymentioning
confidence: 99%